Probabilidades de ocorrência de deficiência hídrica nos solos da região central do Rio Grande do Sul - Cardoso, Claire Delfini Viana (2005)
The detailed determination of the probabilities of occurrence of certain levels of water deficit (WD) is important for the farming planning and environmental management in the public and private administration. Such information not available for the central region of Rio Grande do Sul State. The objective of this study was to determine the total and maximum water deficits, the probability of their occurrence at different levels in a month, ten- and fifteen- day periods basis during the year, for different soils of the central region of Rio Grande do Sul State, under the scope of the meteorological station of Santa Maria (MSSM), to adjust techniques of geoprocessing for their spatialization and to evaluate the differences due to the adoption of daily, ten days or monthly periods of sequential water balance (SWB), and the use of two potential evapotranspiration estimation (ETP) methods. Daily meteorological data measured in the MSSM from August of 1968 to July of 2004 where used to calculate the ETP, with Penman-Monteih, Penman and Thornthwaite methods. The WDs were determined by SWB, for daily, ten days and monthly periods, for different capacities of available water storage (CAS) of region soils, obtained with the application of pedotransfer equations to the physical properties of each horizon and considering the depth of the soil explored by the native vegetation roots. For total WD values (TWD) and maximums (MWD) of each period, higher than 50, 40, 20, 10 and 5mmdistribution functions were adjusted and the probabilities of its occurrence for each five days, ten days or month periods in different soils were obtained and geographic distribution of values was done by geoprocessing techniques. It was verified that the monthly and ten days period values of WD of the soil adjusted to the log-normal, gamma and exponential functions, whit the best adjustment obtained with the log-normal for the months with higher WD and whit the gamma function for the months of lower WD of autumn, winter and spring. Shalower soils (Charrua) had the lower CAD, 40mm, and deepest ones (Cerrito) 215mm. In April and August months, there was not significant risk of WD, mainly in soil with the higher CAD. The probability of occurrence of MWD, accumulated during continuous periods without rain (pDHM), is a function mainly of the period of the year and the CAD of the soil: in soils with lower CAD, pDHM > 50mm is higher in December and January (18%), about 10% in November and lower than 5% in the other months, null from April to September; in soil of higher CAD, pDHM >50mm does not exceed 1.7% of the years in any month, but it raises with the reduction of the MWD to 40, 20, 10 and 5mm. There is not clear relationship betwen variation of the probability differences of occurrence between TWD and MWD and the CADs of the soil; the differences tend to be more related to the magnitude of the probabilities, mainly for deficiencies higher than 50, 40 and 20mm; the difference of probability between TWD and MWD is higher, depending on how high are the occurrence probabilities. In the periods of higher WD, pDHTs of ten days period for the different soil are lower then pDHMs of ten days period, decreasing to less than 5% from April to September and with increase of CAD. pDHT in fifteen days periods does not reach high values as in monthly and ten days periods, because of the lower number of considered days; the distribution of the deficiencies during the year is similar to other periods (monthly and ten days), MWD and TWD, but with better definition of beginning and end of the periods wiht different levels of WD. The monthly ETP estimated by Thornthwaite method is higher than the monthly total of the daily values of ETP estimated by the Penman method from January to July, but are not different from September to November. Decreasing TWD from 50 to 5mm, monthly probabilities of SWB on a daily basis are higher than SWB on a monthly basis, mainly during spring and summer, with an opposite trend during winter.